Transparent flexible ZnO/MWCNTs/pbma ternary nanocomposite film with enhanced mechanical properties - Han, X.; Zeng, X.; Wang, J.; Kong, D.; Foster, Neil; Chen, J. (Zhongguo Kexue Zazhishe, 2016)
© 2016, Science China Press and Springer-Verlag Berlin Heidelberg. Functional organic-inorganic nanocomposites with high transparency show significant potential application in many fields. However, it is still a great challenge to prepare flexible transparent nanocomposites due to the intrinsic stiffness of the nanoparticles and the poor interaction between nanoparticles and organic matrices. In this work, a transparent ternary nanocomposite film with enhanced mechanical performance is fabricated by two-steps. First, the transparent ternary ZnO/MWCNTs/n-butyl methacrylate (BMA) nanodispersion is prepared by mixing the ZnO/BMA and MWCNTs/BMA dispersions directly. Then, the ternary nanocoposites film is fabricated via in-situ bulk polymerization of the above nanodispersions. As a result, the tensile strength of the ZnO/MWCNTs/poly-n-butyl methacrylate (PBMA) ternary film is enhanced by 42% and the elongation at break is three times that of ZnO/PBMA nanocomposite. The hardness of the film increases from 5B to 1H with 40 wt% ZnO. These results indicate that ZnO and MWCNTs can improve the mechanical properties of the composite significantly. Importantly, the ternary nanocomposite film still remains high transparency and exhibit excellent UV-shielding performance. The as-prepared transparent multifunctional nanocomposite films have promising applications in optical materials and devices, such as optical filters, contact lenses and protection packing.